Shaping the Qualities, Values and Standards of Science. How Reporting Guidelines Improve the Transparency of Biomedical Research - Schniedermann, Alexander (Frontiers in Research Metrics and Analytics, 2022)
What is scientific quality and how can it be achieved? Recent developments in clinical biomedicine gave prominence to transparency as a new core value for scientific research. Without transparency, other characteristics and values remain unknown. But how can abstract concepts and values be implemented in day-to-day scientific practices and what gets lost on the way? In order to answer this question, this study investigates the role of the PRISMA reporting guideline for writing systematic reviews and meta-analyses. By combining a document analysis and expert interviews with its developers, it attempts to bridge the gap between research practice and current modes of evaluation. Beside showing how the guideline was designed to be applicable and acceptable as a new standard, the analysis revealed crucial distinctions between transparency as an abstract quality goal and its practical implementation in the form of specifically formulated rules. Although PRISMA relies on transparency in order to be meaningful, it impurfies the concept in order to circumvent some of its main disadvantages.